CHALLENGES AND GOVERNMENT POLICY SOLUTIONS FOR IMPROVING MANGOSTEEN EXPORT IN INDONESIA - Ahjan, Muhamad; Rizki, Muhamad; Fasyehhudin, Mohammad; Sa’diah, Halimatun (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
The mangosteen fruit has the potential to become a leading export commodity from Indonesia when viewed from the development of export volume, thus requiring proper handling. The decline in Indonesia's export performance in recent years has raised concerns for the government and the business world. The lack of synchronization in regulations (between central and regional authorities and across sectors), transportation security, and non-IT-based documentation processes have created high costs in the shipment process. The author employs a qualitative research method based on philosophy, used to investigate scientific conditions (experiments) where the researcher serves as the instrument. Data collection techniques and qualitative analysis focus more on meaning. There are several obstacles faced by Indonesia that need improvement for the successful implementation of mangosteen export, namely Machine/Technology Factors, Price Factors, Marketing Factors, Process Factors, Productivity and Quality Factors, and Skills Factors. One of the solutions implemented by the government is the Indonesian government's policy to enhance productivity and production efficiency, quality, and the appearance of products that meet standards and are attractive to consumers, as well as ensuring production/supply continuity.